Implementasi Peraturan Menteri Agama No. 46 Tahun 2014 Tentang Biaya Nikah Luar Kantor Di Wilayah Kabupaten Ponorogo - Muhammad Riza; Chamila Karuniawati (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2020)
Abstract Regulation of the Minister of Religious Affairs No. 46 year 2014 governs the cost of marriage outside the office which is the prospective bride shall deposit the marriage fee or refer to the account of Treasurer amounting to Rp. 600,000, 00 (six hundred thousand Rupiah). The honorarium of the Penghulu is determined by the typology of the Office of Religious Affairs (KUA) of each region.In the region of Ponorogo Regency there are areas whose geographical conditions are easy to reach such as in the area of urban areas, and which is difficult to reach because it is located within the suburbs that have high enough plains, such as in the Office of Religious Affairs (KUA) subdistrict Pudak, Sooko and Ngrayun. From different geographical circumstances in Ponorogo District, the implementation of marriage and the determination of the cost of marriage in Ponorogo Regency is in accordance with the regulation of the Minister of Religious Affairs No. 46 year 2014 or not. This research uses field research method, which is the researcher plunging directly into the area of research, to obtain related data about the typologies of the Office of Religious Affairs (KUA) of the subdistrict of Pudak, Sooko and Ngrayun, the cost of marriage and the implementation of marriage outside the office in the region Ponorogo Regency. By using the field research, the results found that the implementation of marriage, especially in sub-district Pudak, Sooko and Ngrayun based on conditions and circumstances of the Community in accordance with the regulation of the Minister of Religious Affairs No. 46 year 2014. The determination of the marriage fee in the Office of Religious Affairs (KUA) of the district of Pudak, Sooko and Ngrayun Although the geographical condition is very different from the condition of the other region remains likened, namely Rp. 600,000, 00 (six hundred thousand Rupiah). Abstrak Peraturan Menteri Agama No. 46 tahun 2014 mengatur terkait biaya nikah luar kantor yaitu calon pengantin wajib menyetorkan biaya nikah atau rujuk ke rekening bendahara sebesar Rp.600.000,00 (enam ratus ribu rupiah). Adapun besaran honorarium penghulu ditentukan berdasarkan tipologi Kantor Urusan Agama (KUA) masing-masing wilayah.Di wilayah Kabupaten Ponorogo terdapat daerah-daerah yang kondisi geografisnya mudah untuk dijangkau seperti di daerah sekitar perkotaan, dan yang sulit untuk dijangkau karena berada dalam daerah pinggiran yang memiliki dataran yang cukup tinggi, seperti di Kantor Urusan Agama (KUA) Kecamatan Pudak, Sooko dan Ngrayun. Dari keadaan geografis yang berbeda-beda pada wilayah Kabupaten Ponorogo tersebut pelaksanaan nikah serta penentuan biaya nikah di wilayah Kabupaten Ponorogo apakah sudah sesuai dengan Peraturan Menteri Agama No. 46 tahun 2014 atau belum.Penelitian ini menggunakan metode penelitian lapangan (field research) yaitu peneliti terjun langsung ke daerah obyek penelitian, untuk memperoleh data yang berhubungan tentang tipologi Kantor Urusan Agama (KUA) Kecamatan Pudak, Sooko dan Ngrayun, biaya nikah dan pelaksanaan nikah luar kantor di wilayah Kabupaten Ponorogo. Dengan menggunakan metode (field research), hasil penelitian menemukan bahwa pelaksanaan nikah khususnya di Kecamatan Pudak, Sooko dan Ngrayun berdasarkan kondisi dan keadaan masyarakat kecamatan sesuai dengan Peraturan Menteri Agama No. 46 tahun 2014. Penentuan biaya nikah di Kantor Urusan Agama (KUA) kecamatan Pudak, Sooko dan Ngrayun walaupun kondisi geografisnya sangat berbeda dengan kondisi wilayah yang lainya tetap disamakan, yaitu Rp.600.000,00 (enam ratus ribu rupiah).